"Gendering" European security: policy changes, reform coalitions and opposition in the OSCE. Issue 1 (2nd January 2018) - Jenichen, Anne; Joachim, Jutta; Schneiker, Andrea
ABSTRACT: The Organisation for Security and Co-operation in Europe (OSCE) has rarely been considered in scholarship on gender and security, even though it was one of the regional security organisations whose gender policy predated the United Nations Security Council's call for more international attention to issues related to women, peace and security in October 2000. Based on an analysis of official OSCE documents and on semi-structured interviews, we trace the integration of gender issues in the OSCE and explore the rationale behind and the challenges associated with it. We identify two phases of gender policy change in the OSCE and show how the integration of UNSCR 1325 brought about an expansion of OSCE gender policy from an exclusive focus on "soft" security issues towards increased inclusion of gender in the area of "hard" security. Drawing on historical and feminist institutionalism, we argue that reform coalitions were crucial for the policy changes in the OSCE but that they encountered institutional and ideational barriers, which hampered implementation of the gender policy. In light of rising opposition, our analysis warns of a backlash that might jeopardise current achievements.